2011
DOI: 10.1093/ejechocard/jer176
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular hypertrophy reclassification and death: application of the Recommendation of the American Society of Echocardiography/European Association of Echocardiography

Abstract: In a large cohort study of unselected adult outpatients referred to the echocardiography laboratory, the measurements of indexed LV mass applying the ASE/EAE recommended cut-offs yielded remarkable discrepancy in the diagnosis of LVH severity and offered prognostic information beyond that provided by septal thickness only criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 28 publications
4
44
0
1
Order By: Relevance
“…In keeping with the results by Barbieri et al, 28 our study extends to a general population the notion that LVH as defined by linear dimensions of LV wall thickness has no independent value in predicting cardiovascular outcomes. At variance from the above-mentioned study investigating the predictive value of single linear LV parameter (IVS), 28 our analysis included also PW thickness, the sum of IVS plus PW thickness, and RWT. The lack of a significant relationship between these linear LV measurements and cardiovascular prognosis in our study may have multiple explanations.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In keeping with the results by Barbieri et al, 28 our study extends to a general population the notion that LVH as defined by linear dimensions of LV wall thickness has no independent value in predicting cardiovascular outcomes. At variance from the above-mentioned study investigating the predictive value of single linear LV parameter (IVS), 28 our analysis included also PW thickness, the sum of IVS plus PW thickness, and RWT. The lack of a significant relationship between these linear LV measurements and cardiovascular prognosis in our study may have multiple explanations.…”
Section: Discussionsupporting
confidence: 89%
“…More recently, an observational study by Barbieri et al that included 2,445 adults referred to a single-center echocardiographic laboratory for unselected indications showed that LVH, as defined by sex-specific cutoffs of IVS thickness recommended by the ASE/EAE guidelines, was unrelated to allcause death during a mean follow-up period of 2.5 years. 28 In contrast, LV mass/BSA values retained a significant, graded association with total mortality after adjustment for age, sex, LV ejection fraction, presence of moderate valve disease, and atrial fibrillation. In keeping with the results by Barbieri et al, 28 our study extends to a general population the notion that LVH as defined by linear dimensions of LV wall thickness has no independent value in predicting cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…LV mass index might have been a better tool to exclude LV hypertrophy than the determination of septal wall thickness. However, it seems that the inferiority of septal wall thickness versus LV mass index is less when only excluding rather than grading LV hypertrophy severity (31).…”
Section: Study Limitationsmentioning
confidence: 99%
“…It is also well recognised that infants born to diabetic mothers have cardiomegaly, even after controlling for birth weight (7,8). The presence of left ventricular hypertrophy (LVH) can be potentially life threatening and has been associated with the risk of sudden death, often due to arrhythmias (9,10). Therefore, patients with CHI may be at risk of significant cardiac morbidity, particularly in longterm follow-up.…”
Section: Introductionmentioning
confidence: 99%